2010
DOI: 10.1248/bpb.33.1355
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phthalide Compounds from <i>Sparassis crispa</i> (Hanabiratake), Hanabiratakelide A&mdash;C, Exhibiting Anti-cancer Related Activity

Abstract: Sparassis crispa (SC), known as Hanabiratake in Japanese, is an edible mushroom with various medicinal properties. We isolated 3 novel phthalides, designated hanabiratakelide A (1), B (2), and C (3), from the SC fruit body. In this investigation, 3 known phthalides (4-6), ubiquinone-9, and 2 known unsaturated fatty acids were also isolated. Their structures were elucidated primarily through extensive NMR experiments. The isolated compounds 1-6 were tested for their anti-oxidant activity. The in vitro superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 30 publications
0
31
0
2
Order By: Relevance
“…Yoshikawa et al isolated three novel phthalides, designated hanabiratakelide A (8), B (9), and C (10) in addition to three known phthalides, from the S. crispa fruiting body [34]. The 6 isolated compounds were tested for their antioxidant activity.…”
Section: Chemical Constituents and Bioactive Components Of S Crismentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshikawa et al isolated three novel phthalides, designated hanabiratakelide A (8), B (9), and C (10) in addition to three known phthalides, from the S. crispa fruiting body [34]. The 6 isolated compounds were tested for their antioxidant activity.…”
Section: Chemical Constituents and Bioactive Components Of S Crismentioning
confidence: 99%
“…S. crispa feeding dose-dependently suppressed the malignant changes of ACF by 54% (0.3% group), 64% (1.0% group), and 75% (3.0% group). They concluded that the anticancer-related activity may originate from the aforementioned hanabiratakelides [34]. …”
Section: Pharmacological Aspects Of S Crispamentioning
confidence: 99%
“…The results obtained from headspace analysis indicate that 3-octanone, DL-3-octanol, and 1-octen-3-ol contribute to the particular aroma of this mushroom [4]. Medicinal properties in S. crispa include anticancer activities‚ antiangiogenic‚ anti-metastatic, wound healing and immune stimulation effects [5]- [7]. It has been recorded that β-glucan content of S. crispa is about 43.6% as measured by enzyme method by Japan Food research laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Сучасні відомості щодо лікувальних властивостей S. crispa свідчать про широкий біологічний спектр дії цього гриба (Tada et al, 2007;Dalonso et al, 2015). Встановлено, що екстракти, отримані як з плодових тіл, так і міцеліальної маси даного виду, мають імуномодулюючий, онкостатичний і антиметастатичний ефекти (Woodward et al, 1993;Kwon et al, 2009;Yamamoto et al, 2009;Yoshikawa et al, 2010;Takashi, 2013). За умов глибинного і поверхневого культивування штами S. crispa здатні до біосинтезу антибіотиків і цитокінінів (Dyakov et al, 2011;Vedenicheva et al, 2016).…”
unclassified